Characterization of polymorphic HERV-K (HML-2) endogenous proviruses in human and gorilla genomes. - Freeman, Michael. (Tufts University. Tisch Library., 2019)
The HERV-K (HML-2) endogenous retrovirus (ERV) family is the most recently active group of ERVs in humans, being the only group with human-specific insertions. Some of the human-specific HERV-K (HML-2) proviruses have retained one or more viral open reading frames (ORFs) and have remained insertionally polymorphic in the human population, hinting at recent activity in our lineage. Furthermore, there is a strong correlation between HML-2 expression and cancerous and inflammatory disease states. Though no naturally infectious HML-2 proviruses are known, there is the possibility that some undiscovered HML-2 proviruses may still be active in the human population. Our group used publicly available human genomic data from diverse populations in an effort to data-mine for these uncharacterized, insertionally polymorphic HML-2 elements. This search resulted in the discovery four non-reference HML-2 alleles that were carried at a very low frequency within our population. One of these four alleles, Xq21.33, contained an ORF for every viral gene, making it the second known example of a full-length endogenous HML-2 provirus. We investigated the function of this full-length provirus and found that it retained some of the functions necessary for viral replication. Namely, the LTRs were active promoters, the provirus could splice the three requisite viral transcripts, and the provirus could produce retroviral-like particles and encapsidate the genomic viral RNA. Unfortunately, the internal gag, pol, and env sequences of this provirus were found to contain deleterious mutations that render Xq21.33 not infectious. Targeted reversion of these substitutions revealed that only 6 point mutations distinguish Xq21.33 from a replication-competent provirus, indicating that these elements may be closer to viable than we expect. After data-mining over 2500 individual genomes, we were unable to identify a viable HML-2 provirus in the human population. Since the HML-2 family is not restricted to our lineage, we expanded the search to our close hominin relative, the gorilla. Using a combination of the junction discovery method and linker-mediated integration site analysis, we identified 31 novel 2-LTR proviruses in the gorilla genome. We found that the gorilla-specific HML-2 elements contained many features that are indicative of a recently active clade of endogenous retroviruses: there is little divergence within the sequences of the proviruses, the proviruses remain insertionally polymorphic in the population, and many proviruses encode intact ORFs for viral proteins. We examined the 31 novel HML-2 elements and determined that the gorilla-specific proviruses retained much more activity than their human counterparts. Six gorilla HML-2 loci were found to have a functional, fusogenic envelope glycoprotein, three loci were found to produce viral particles with an active reverse transcriptase, and two loci could produce particles that mediated infectious gene transfer. Although no provirus identified in the human or gorilla screens is expected to produce a replication competent HML-2 element on its own, we did identify a number of partially functional gorilla-specific HML-2 proviruses which retained an active envelope or viral core. Some of these partially infectious HML-2 elements reside in the same gorilla genomes, hinting at the potential for current replication in the gorilla population.; Thesis (Ph.D.)--Tufts University, 2019.; Submitted to the Dept. of Biochemistry.; Advisor: John Coffin.; Committee: Jim Baleja, Claire Moore, and James Munro.; Keyword: Virology.